Management and utilization of crossbred bullocks under field conditions - REDDY, A O; SREEKUMAR, D; RAO, M K (The Indian Journal of Animal Sciences, 2013)
Management and utilization patttem of crossbred bullocks at a few locations around Bangalore (Karnataka) and Kerala were studied. Irrespective of size of tho land holding all cataegories of farmers used crossbred bullocks for a variety of agricultural operations. Farmers procured crossbred bullocks mostlylocally from other farmers. Selection of these bullocks was usually based on general appearance, body conformation and positioning of whorls. Most of the fanners interviewed sought advice from others in selecting the animals. "Temperament" of the bullocK was not an imponant criterion for selection as thecrossbred bullocks were generally docile. The average price of a pair crossbred bullocks was Rs 4042.8 and the prices ranged from Rs 1 600 to Rs 10 000. The farmers found them to be cheaper than zebu bullocks. Farmers around Bangalore utilized the bullocks throughout the year@ 8-10 hr/day. Total utilization hours in Kerala were about 775 hr/annum. Most of the farmers allowed their bullocks to sustain only on paddy/ fingermillet straw supplemented with grazing during monsoon. The large farmers around Bangalore also fed 2-3 kg of concentrates along with the straw.